Cardiovascular manifestations in hyperthyroidism - Kandan, Vairamani; P., Sathyamurthy; M., Rajkumar; Narayanan, Lavanya (International Journal of Research in Medical Sciences, 2017)
Background: It is well known that thyroid hormone directly affects the heart and peripheral vascular system. In hyperthyroidism, cardiovascular manifestations are frequent findings. Atrial arrhythmias, limitations in exercise tolerance, and congestive heart failure were reported to occur more common in older patients as a result of hyperthyroidism. Cardiovascular signs of hyperthyroidism include tachycardia, widened pulse pressure, marked increase in cardiac output with impaired cardiovascular and respiratory exercise capacity. Most of the cardiac abnormalities return to normal once a euthyroid state has been achieved in a majority of patients. There are very few studies which address the most important cardiovascular manifestations of hyperthyroidism particularly in Indian population. Hence this study is aimed at addressing this area. The aim was to study the prevalence of various cardiac manifestations in overt and subclinical hyperthyroidism. Methods: 50 patients of hyperthyroidism who visited general medicine department of Sri Ramachandra Medical College, Chennai, India was included in the study. Patients with other co-morbidities which could contribute to cardiovascular manifestations were excluded from the study. All the patients underwent clinical evaluation, basic laboratory tests like CBC, RFT, LFT, serum electrolytes, fasting lipid profile (which included serum triglycerides, LDL, HDL, total cholesterol), FT4, FT3 and TSH and radiological variables were studied in these patients. ECG and 2D ECHO were performed in these patients to analyze the presence of any cardiac manifestations in these patients.. Results: In this study females (60%) were more than males (40%), commonest cardio vascular symptoms were palpitation (78%), followed by dyspnoea (26%) and chest pain (4%). The commonest cardio vascular signs were found to be tachycardia (82%), widened pulse pressure (50%) and pedal edema (12%). The commonest ECG finding was found to be Sinus tachycardia (46%) followed by atrial fibrillation (28%), Non-Specific ST-T changes, left ventricular hypertrophy, RV hypertrophy and RBBB. Systolic dysfunction and chamber enlargement (18%) were the commonest echo findings. Conclusions: This study shows that cardiovascular manifestations are quite common and varied in hyperthyroidism which are to be looked for in the management.